Mitigasi Volatilitas Transfer Pricing: Bukti Empiris Robustitas Interquartile Range Melalui Simulasi Data Ekstrem - FX Willy Ari Pamungkas; Novera Ermina Putri; Poltak Maruli John Liberty Hutagaol (Universitas Muhammadiyah Ponorogo, 2026)
This study evaluates the robustness of the Interquartile Range (IQR) method in determining the Arm's Length Range for transfer pricing compliance within the Indonesian food and beverage industry. Considering the complexity of affiliate transactions in the manufacturing sector which often results in non-normally distributed margin data, selecting the appropriate statistical method is crucial to avoid tax dispute risks. Utilizing empirical data from 52 observations and implementing stress-testing scenarios with extreme margin interventions (1% to 3%), this research assesses the stability of the central tendency against various market anomalies. Following the OECD Transfer Pricing Guidelines and PMK 172/2023, the calculation employs linear interpolation to establish precise quartile boundaries (Q1 and Q3). The results indicate that the IQR method effectively mitigates the impact of extreme outliers, maintaining a more stable compliance zone compared to conventional arithmetic mean approaches. The findings confirm that integrating stress-test scenarios in transfer pricing documentation provides a scientifically valid defense against aggressive tax audits, ensuring multinational enterprises report fair taxable profits reflecting actual economic activities.